Carbon fixation of CO2 via cyclic reactions with borane in gaseous atmosphere leading to formic acid (and metaboric acid); A potential energy surface (PES) study - Mohammadi, Marziyeh; Siadati, Seyyed Amir; Ahmadi, Sheida; Habibzadeh, Sepideh; Poor Heravi, Mohammad Reza; Hossaini, Zinatossadat; Vessally, Esmail (Frontiers in Chemistry, 2022)
Carbon dioxide (CO2), this stable gaseous species is occupying the troposphere layer of atmosphere. Following it, the environment gets warmer, and the ecosystem changes as a consequence of disrupting the natural order of our life. Due to these, in the present project, the possibility of carbon fixation of CO2 by using borane was investigated. To do this, each of the probable reaction channels between borane and CO2 was pursued to find the fate of this species. The results indicate that among all channels, the least energetic way for the reaction is reactant complex (RC) to TS (A-1) to Int (A-1) to TS (A-D) to formic acid (and further meta boric acid production from transformation of boric acid). It shows that the use of gaseous borane might lead to control this dangerous greenhouse gasses which are threatening the present form of life on earth, our beautiful fragile home.